As representações históricas do orientalismo na Obra de Tolkien (1930 1950) - Átila Siqueira Martins Lopes (2016)
This present work aims at questioning Tokien‘slitrary work about the Middleearth, with the objective of identifying, in the plot different positive representations about the western Europeans and pejorative about the eastern ones. This way, through the analysis of this author‘s texts, there is a search for the comprehension of the way this author presents the ideas of civilization and barbarism, superior and inferior race and the West as a superior place and the East as an inferior place. These evaluating forms to deal with the West and the East are addressed in Tolkien‘s literary works as a representation of ideas which were around in the period of his intellectual formation an writing. This way, his literary work will be analyzed aiming at understanding the light of the most recent studies about Orientalism, Alterity,Ethnocentrism and Eurocentrism, the influence of ideas from his time, by him confirmed.